GROWTH AND NUTRITION OF Paratecoma peroba SEEDLINGS IN DIFFERENT TUBE VOLUMES AND CONTROLLED-RELEASE FERTILIZERS - Feletti, Thais Arão; Araújo, Emanuel França; Gonçalves, Elzimar de Oliveira; Feletti, Thamara Arão; dos Santos, Aline Ramalho; Gibson, Elbya Leão (Floresta, 2020)
Paratecoma peroba is a native forest species of great economic and ecological interest, currently at risk of extinction from selective and illegal exploitation; however, there are no established parameters for the production of seedlings of this species. The objective of this study was to analyze the growth and nutritional balance of P. peroba seedlings grown in polypropylene tubes of different sizes with variable doses of controlled-release fertilizer (CRF). Three volumes of tubes (120, 180, and 280 cm3), four CRF doses (0, 2.5, 5, and 7.5 kg m-3), and a conventional mineral fertilizer (CF) were tested as indicated in the literature for native forest species: arranged in a completely randomized design in a 3 × 5 factorial scheme, with four replicates composed of 16 seedlings. After 180 days, the percentage of survival, growth variables, indices of the diagnosis and recommendation integrated system, and the average nutrient balance index of the seedlings were analyzed. Based on the total dry matter and the mean nutritional balance index, the combination of a 280 cm³ tube with a 7.5 kg m-3 CRF dose was the most effective in the production of P. peroba seedlings.